Menstrual hygiene practices and constraints in availing government sanitary pad provision among adolescents in rural Puducherry: A mixed method study - Gayathri Surendran; Mamta Gehlawat; Shanthosh Priyan; Sonali Sarkar (Wolters Kluwer Medknow Publications, 2021)
Context: Although free and subsidized sanitary pads are provided by the government, proportion of adolescents availing this service remains low. Aims: The aim of the study was to determine the proportion of adolescent girls availing supply of sanitary napkins from a rural health training center (RHTC) in Puducherry; to assess the level of satisfaction with government supply; and to identify reasons for not accessing the same. Subjects and Methods: The mixed-method cross-sectional study done in July 2017 included 240 adolescent girls living in the RHTC service area of a tertiary care institute. Quantitative data were collected house to house with a pretested semi-structured questionnaire and qualitative data from a focused group discussion. Results: Sanitary pads were used by all of the participants who achieved menarche. Of them, 87 (40.2%) used pads purchased outside and 127 (58.8%) used both government supply and private purchase. Reasons for not availing government supply were insufficient quantity and low quality, lack of information about the government provision, and accessibility issues. Conclusions: Ensuring better quality and adequate quantity of sanitary pads supplied by the government along with increased awareness about the government provision can increase the utilization of the same by rural adolescents.